Water for life in Alberta, Canada: Assessing First Nations engagement - Schultz, Juliane; Baijius, Warrick; Patrick, Robert J (Canadian Planning and Policy / Aménagement et politique au Canada, 2023)
Water is integral to Alberta’s economy, grounded in agriculture, power generation, extractive industry, tourism, and recreation. In 2003, the Government of Alberta released the Water for Life Strategy (the Strategy) amidst growing public concerns over multiple impacts on provincial water resources. The Strategy is a framework document guiding the development of watershed plans across the provincial landscape to be implemented by Watershed Protection and Advisory Committees (WPACs). This paper explores the extent to which First Nations in Alberta were included in the government’s development of the Strategy and in the implementation of the Strategy by the WPACs. Our research data was gathered through key informant interviews with WPAC personnel as well as content analysis of relevant planning documents from provincial and WPAC sources. The research results point to an absence of First Nations inclusion in both the development of the provincial water Strategy as well as the implementation of the Strategy through the WPAC policies and plans. The results also identify institutional gaps and opportunities by which the provincial government and the WPACs may engage more effectively and inclusively with Indigenous communities. From our analysis, we recommend a series of institutional arrangements to advance far greater inclusion of Indigenous voices and recognition of Indigenous peoples as rights-holders, in watershed planning in Alberta.